'Ace' forage cowpea. Issue 2 (7th May 2020) - Smith, G. R.; Rouquette, F. M.; DeLaune, P.
Abstract: 'Ace' (Reg. no. CV‐329, PI 691530) is a small‐seeded cultivar of forage cowpea [ Vigna unguiculata (L.) Walp.] that was developed by Texas A&M AgriLife Research at Overton, TX. Ace is intended for use in wildlife supplemental plantings, cover cropping systems, and hay production systems. Forage cowpeas are widely used in Texas and the U.S. southern region as supplemental plantings for white‐tailed deer, but seed production of late‐flowering forage cowpeas is restricted in northern Texas due to freeze kill prior to seed maturity. Mass selection within two highly variable plant introduction lines was used to develop Ace. Seed from five plants with very similar phenotypes, including first bloom in late August, was bulked and tested as experimental forage cowpea. Biomass production of Ace (experimental designation TX‐3) at Overton was 2.8 and 4.7 Mg ha −1 in 2013 and 2015, respectively. Biomass production of Ace at Vernon, TX, in 2015, 2016, and 2017 was 3.9, 5.9, and 6.7 Mg dry matter ha −1, respectively. Protein content of Ace biomass at Vernon in 2015 and 2016 was 16.5 and 16.4, respectively. Seed production of Ace at Vernon ranged from 106 to 670 kg ha −1 . The seed size of Ace, expressed as seed weight, was 5.1 g 100 seeds −1, compared with Iron & Clay at 10.6 g 100 seeds −1 . Average days to first bloom at Overton for Ace and Iron & Clay are 87 and 114, respectively. Root galling of Ace by southern root‐knot nematode ( Meloidgyne incognita Race 3) is very low, and nematode reproduction is low, relative to southern root‐knot nematode–susceptible cowpea lines. Greenhouse seed germination studies indicate about 25% of Ace seed would survive after 2 mo of simulated field conditions and that all seed would be germinated after 3 mo. The reseeding potential of Ace needs further study.